Early Childhood Education in the Perspective of Luqman al-Hakim - Dewi Astuti; Sanusi Makhda (HADHANATUNA: Journal of Early Childhood Education, 2025)
This study explores early childhood education from the perspective of Luqman al-Hakim as presented in Surah Luqman (12–19), emphasizing the integration of spiritual, moral, emotional, and social development within a holistic Islamic framework. Using a qualitative, textual, and thematic analysis approach, the research examines Luqman’s counsel as a model of value-based education rooted in tawhid, gratitude, moral discipline, humility, parental guidance, and social responsibility. The findings reveal that faith formation is positioned as the foundational dimension of a child’s development, shaping worldview, ethical identity, and behavioural orientation. Parental involvement emerges as the central mechanism of early education, characterized by wisdom-based dialogue, compassion, and exemplary conduct. The guidance of Luqman is shown to function as an early model of character education that aligns with contemporary holistic education principles, demonstrating the relevance of classical Islamic pedagogy to modern discourse. This study suggests that Luqman’s educational philosophy offers a meaningful framework for designing spiritually grounded and ethically responsive early childhood programs in Muslim contexts. By restoring the balance between intellectual growth and moral-spiritual formation, Luqman’s perspective contributes a timeless paradigm for nurturing dignified, reflective, and socially responsible children in today’s world.